Research on Portal Venous Hemodynamics and Influencing Factors of Portal Vein System Thrombosis for Wilson’s Disease after Splenectomy - Zheng, Zhou; Yu, Qingsheng; Peng, Hui; Zhang, Wanzong; Shen, Yi; Feng, Hui; Huang, Long; Zhou, Fuhai; Zhang, Qi; Wang, Qin (Frontiers in Surgery, 2022)
Objective: Splenectomy is one crucial solution for hypersplenism with portal hypertension. However, portal vein system thrombosis (PVST) caused by hemodynamic changes affects the prognosis of patients. We analyze the changes in portal vein hemodynamics following splenectomy for Wilson's disease combined with portal hypertension and the influencing factors that lead to PVST. Methods: A retrospective cohort study was conducted, in which 237 Wilson's disease patients with hypersplenism underwent splenectomy. The hemodynamic indexes of portal vein were monitored before surgery and on the 1st, 7th, and 14th days around surgery. The patients were divided into PVST and non-PVST groups. The clinical factors were identified by univariate and multivariate Logistic regression. The logit P was calculated according to logistic regression prediction model, and ROC curve for each independent factor was plotted. Results: Portal vein velocity, flow, and inner diameter showed a downward trend around surgery, with statistically significant differences between each time point (P<0.01). PVST incident was 55.7%. Univariate analysis revealed that platelet (PLT) levels on postoperative 3rd and 7th days (P=0.001; P<0.001), D-dimer (D-D) on postoperative 7th and 14th days (P=0.002;P<0.001), preoperative portal vein velocity, flow, diameter (P<0.001), and splenic vein diameter (P<0.001) were statistically significantly different between two groups. Multivariate logistic regression revealed a significant increase in PLT on postoperative 7th day (OR=1.043, 95% CI: 1.027 1.060, P<0.001) and D-D at postoperative 14th day (OR=1.846, 95% CI: 1.400 2.435, P<0.001). Preoperative portal and splenic vein diameters (OR=1.565, 95% CI: 1.213 2.019, P=0.001; OR=1.671, 95% CI: 1.305 2.140, P<0.001) were risking factors of PVST. However, preoperative portal vein velocity and flow (OR=0.578, 95% CI: 0.409 0.818, P=0.002; OR=0.987, 95% CI: 0.975 0.990, P=0.046) were protective factors for PVST. Logit P was calculated using a logistic regression prediction model with a cut-off value of -0.32, an area under receiver operating characteristic curve of 0.952 with 88.61% accuracy. Conclusions: Splenectomy relieves portal hypertension by reducing hemodynamics index. PVST is linked to multiple factors, including preoperative portal vein diameter, velocity, flow, and splenic vein diameter, especially PLT on postoperative 7th day and D-D on postoperative 14th day. The predictive model is accurate in predicting PVST.